PEMIKIRAN ABDURRAHMAN WAHID TENTANG DEMOKRASI PLURALISTIK DAN PENGARUHNYA DI INDONESIA - Jannah, Wirdatul; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to find out the thoughts of Abdurrahman Wahid about pluralistic democracy and its influence in Indonesia. Pluralistic democracy is a theory initiated by Robert A. Dahl. Therefore, the formulation of the problem in this research is what Abdurrahman Wahid's thinking about pluralistic democracy and its influence in Indonesia. This research uses qualitative research approach with descriptive research type with data collection is done by method of research library.From the results of the research shows that Abdurrahman Wahid is an Indonesian intellectual figure who expressly accepted democracy as a final preference for a political or state system especially in Indonesia which has a diversity of ethnic groups. Abdurrahman Wahid stated that democracy must be accompanied by the recognition of plurality, social justice, economically, politically, and legally so that the unity of Indonesia remains intact within the Unitary State of the Republic of Indonesia. Democratic values such as social justice, freedom, recognition of individual rights, and social norms and local wisdom of the Indonesian nation must be fought for the life of the nation.Keywords: Pluralistic Democracy, Abdurrahman Wahid, Political Thought